New headquarters of the Provincial Municipality of Tacna to achieve levels of efficiency in local management and governance - Calizaya Herrera, Lucía Vilena (2014)
Objective: We now know that a local or municipal government seeks the Mayor govern its functions efficiently, that's why seeks Formulate and develop the architectural design of the new headquarters of the Provincial Municipality of Tacna to achieve levels of efficiency in the management and local governance in response to the current infrastructure deficit.Method: The methodology used was descriptive research because it will allow us to know the situations, customs and prevailing attitudes through the exact description of the activities, objects, processes and people and it is also explanatory because it is the organized set of principles, inferences, beliefs , discoveries and claims, by which a reality is interpreted.Results: As a result of the diagnosis and analysis was considered very necessary and urgent that a New Head Provincial Municipality of Tacna is built given the overcrowding of virtue that not every area has its own work area, causing a total disorder for both staff and visitors demanding the attention of the same.Conclussion. In the process of research we can conclude that is oriented to formulate, initiate and develop the architectural project as proposed to face the deficit of the current infrastructure of the Provincial Municipality of Tacna.